Conflitos familiares e vulnerabilidade social - Fontanella, Beatriz (My University, 2019)
Conflict can be present in all types of relationships and in all societies, considering that it can be understood as a failure or rupture of communication, and may have traumatic consequences for those involved, where they find it difficult to fulfill their basic socialization tasks and amparo. Thus, situations of vulnerability are established, thus weakening family ties, affecting the harmony and healthy development of family members. Having said this, the present Work of Course Completion has as general objective to identify interventions of the psychologist to mediate family conflicts in situation of social vulnerability. This study also proposes as specific objectives to conceptualize family, to characterize family conflicts, to define social vulnerability, to describe the concept of mediation and to describe the possible attributions of the psychologist. The work has as a delineation a qualitative exploratory research. Scientific articles were used as source. Subsequently, a table was prepared to organize the relevant data on these articles. The framework of analysis chosen was the integrative synthesis. From the collected data, it was possible to perceive that conflicting family relationships cause harm to the involved, causing damages, generating instability and insecurities, especially if they have smaller children, they can be affected in their development and weakening their bonds, being these essential for emotional balance. The moment the conflict is established, family life becomes unfeasible, causing a transformation in this family due to undesirable dissatisfactions and disagreements. In this way, the importance of psychologist intervention is highlighted, in order to promote and encourage good interpersonal relationships, promoting opportunities for the development of the communication process that may help the people involved to find solutions to their conflicts. [resumo fornecido pelo autor]
O conflito pode estar presente em todos os tipos de relacionamentos e em todas as sociedades, considerando que possa ser compreendido como uma falha ou ruptura de comunicação, podendo ter consequências traumáticas para os envolvidos, onde os mesmos encontraram dificuldades para cumprir suas tarefas básicas de socialização e de amparo. Sendo assim, situações de vulnerabilidade são instauradas, fragilizando assim os vínculos familiares, afetando a harmonia e o desenvolvimento saudável dos membros do grupo familiar. Tendo isto posto, o presente Trabalho de Conclusão de Curso tem como objetivo geral identificar intervenções do psicólogo para mediar conflitos familiares em situação de vulnerabilidade social. Este estudo também propõe como objetivos específicos conceituar família, caracterizar conflitos familiares, definir vulnerabilidade social, descrever o conceito de mediação e descrever as possíveis atribuições do psicólogo. O trabalho possui como delineamento uma pesquisa qualitativa de caráter exploratório. Foi utilizada como fonte artigos científicos. Posteriormente, foi construída uma tabela para organização dos dados relevantes sobre estes artigos. O referencial de análise escolhido foi a síntese integradora. A partir dos dados coletados, foi possível perceber que as relações familiares conflituosas causam danos aos envolvidos, provocando prejuízos, gerando instabilidade e inseguranças, especialmente se possuem filhos menores, os mesmos podem ser afetados em seu desenvolvimento e fragilizando os seus vínculos, sendo estes essenciais para o equilíbrio emocional. No instante que o conflito é instaurado, torna-se inviável o convívio familiar, causando uma transformação nesta família, devido as insatisfações e desavenças indesejáveis. Desta forma, destaca-se a importância da intervenção do psicólogo, a fim de promover e incentivar o bom relacionamento interpessoal, promovendo oportunidades para desenvolvimento do processo de comunicação que poderá auxiliar as pessoas envolvidas a encontrarem soluções para seus conflitos. [resumo fornecido pelo autor]
Keywords: Família; Mediação familiar; Vulnerabilidade social; Psicologia